The Politics of Computer Music - Iazzetta, Fernando (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
When a set of objects, actions, and procedures begin to coalesce and gain some coherence, they become perceived as a new, cohesive field. This may be related to the emergence of a new discipline, a new craft, or a new technological configuration. As this new field shows some coherence and unity, we tend to overlook the conditions that gave rise to it. These conditions become "naturalized" as if they were inherent in that field. From this point on, we do not wonder anymore to what extent the contingencies (formal, social, economic, technological, aesthetic, religious) that gave rise to that field have been crucial to its constitution. When it comes to computer music we are comfortably used to its applied perspective: tools, logical models, and algorithms are created to solve problems without questioning the (non-computational) origin of these problems or the directions taken by the solutions we give to them. The idea of computing as a set of abstract machines often hides the various aspects of the sonic cultures that are at play when we develop tools and models in computer music. The way we connect the development of computer tools with the contingencies and contexts in which these tools are used is what I call the politics of computer music. This connection is often overshadowed in the development of computer music. However, I would like to argue that this connection is behind everything we do in terms of computer music to the point that it often guides the research, development, and results within the field.